HUBUNGAN PEMAHAMAN NILAI-NILAI PANCASILA PADA PEMBELAJARAN PPKn DENGAN KARAKTER SISWA KELAS V SDN GUGUS V AMPENAN - Rizki Amalia Nuraini; Asrin Asrin; Ilham Syahrul Jiwandono (Program Studi PGSD, FKIP, Universitas Mataram, 2021)
This research is motivated by a fairly severe fragility of character, one of which is caused by not optimal character development in educational institutions. Currently, education in Indonesia only focuses on the left brain (hard skills) and does not pay attention to the development of the right brain (soft skills). In addition, the increasing character of the Indonesian nation is not good, especially the character of students who do not reflect the values ​​of Pancasila. Pancasila values ​​are very important values ​​because they contain the noble values ​​of this nation and are very relevant to be used as the basis for shaping the character of the nation. Thus the researcher conducted the research with the aim of knowing whether there was a significant relationship between the understanding of the values ​​of Pancasila and the character of the students. The method used in this research is quantitative methods. The research location at SDN Gugus V Ampenan in class V. The research sample was 55 students. The research instruments used were tests and questionnaires. The data analysis technique used Product Moment Correlation. The results of the calculation with the results of the Correlation Coefficient which is marked with an r value of 0.979 which means that there is a strong relationship between the understanding of the values ​​of Pancasila and the character of the students of SDN Gugus V Ampenan. The results showed that there was a significant relationship between the understanding of Pancasila values ​​and the character of the fifth grade students of SDN Gugus V Ampenan.